The Influence of Talent Management and Knowledge Management on Employee Performance with Employee Engagement as a Mediating Variable at PT. Bank Mandiri Branch, University of North Sumatra - RS, Yoppy Mairizon; Absah, Yeni; Gultom, Parapat (Asian Journal of Management Analytics, 2025)
This study aims to examine the influence of knowledge management and talent management on employee performance, with employee engagement as a mediating variable at PT. Bank Mandiri (Persero) Tbk, University of North Sumatra Branch. Using a quantitative approach, data were collected through questionnaires from 36 employees and analyzed using path analysis with statistical software. The results show that both talent management and knowledge management have significant and positive effects on employee engagement and performance. Furthermore, employee engagement significantly influences performance and mediates the relationship between knowledge and talent management on performance. These findings highlight the importance of effective knowledge and talent management strategies to enhance employee engagement and overall performance.